2014
DOI: 10.1177/0161734613514391
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler Evaluation of the Retrobulbar Hemodynamic Changes in Chronic Obstructive Pulmonary Disease

Abstract: The aim of this study was to evaluate the hemodynamic changes in the extraocular orbital vessels of the patients with chronic obstructive pulmonary disease (COPD), using color Doppler ultrasonography, and to compare the results with those of healthy control subjects. The control group consisted of 35 healthy subjects who had no systemic problems, while the study group consisted of 60 patients with the diagnosis of COPD. Patients with COPD were grouped according to the Global Initiative for Chronic Obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
2
9
0
3
Order By: Relevance
“…Chronic hypoxia and hypercapnia may affect the retinal and choroidal blood flow in COPD patients. In this regard, some color Doppler ultrasonography studies have demonstrated impaired retrobulbar hemodynamics, reduced retrobulbar blood flow, and increased resistance to blood flow in both the retinal and choroidal circulation in COPD patients [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia and hypercapnia may affect the retinal and choroidal blood flow in COPD patients. In this regard, some color Doppler ultrasonography studies have demonstrated impaired retrobulbar hemodynamics, reduced retrobulbar blood flow, and increased resistance to blood flow in both the retinal and choroidal circulation in COPD patients [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meydana gelen kronik hipoksi ve hiperkapninin oküler arterler üzerindeki etkilerini ele alan çalışmalara da literatürde rastlamaktayız [10,11]. Akciğerler ve hava yollarındaki enflamasyonun yanısıra, mekanizması kesin olmamakla birlikte sistemik bir enflamasyon geliştiği de gösterilmiştir.…”
Section: Discussionunclassified
“…Furthermore, no significant differences were found in PSV and EDV between patients with COPD and control subjects (Celik et al. ). However, it has been recognized that both PSV and EDV can be influenced by Doppler angle, whereas RI is independent of the Doppler angle (Platt et al.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in PSV, EDV and RI are associated with various vascular disorders, and have predictive value for coronary artery diseases (Tranquart et al 2003;Maruyoshi et al 2010). Three studies used colour Doppler ultrasonography with patients with COPD, showing an increased PSV, EDV, and RI values of the ophthalmic artery (OA), central retinal artery (CRA) and posterior ciliary artery (PCA) in patients with COPD compared to non-COPD control subjects (Ozer et al 2006;Celik et al 2014;Yakut et al 2015). Ozer et al (2006) determined RI, pulsatility index (PI), PSV and EDV in the OA, CRA and PCA in 45 male patients with COPD and 17 male controls.…”
Section: Colourmentioning
confidence: 99%